Instruments to target agricultural subsidies to desired beneficiaries - Takeshima, Hiroyuki; Lee, Hak Lim (International Food Policy Research Institute, 2012)
The economic characteristics of subsidized inputs affect how the benefits of the subsidy on the input are distributed between farmers and input suppliers. However, how the benefits are distributed across the population of farmers in a country depends largely on the targeting of the subsidy program. Balancing efficiency in the provision of the subsidy with equity in the distribution of the benefits farmers as a whole receive from the subsidy is generally difficult. Trying to achieve both may often end up in achieving neither efficiency nor equity. It is therefore advisable to focus primarily on one of these two principal goals.